Short-Term Investment and the Informational Efficiency of the Market - Vives, Xavier (Review of Financial Studies, 1995)
[A dynamic finite-horizon market for a risky asset with a continuum of risk-averse heterogeneously informed investors and a risk-neutral competitive market-making sector is examined. The article analyzes the effect of investors' horizons on the information content of prices. It is shown that short horizons enhance or reduce accumulated price informativeness depending on the temporal pattern of private information arrival. With concentrated arrival of information, short horizons reduce final price informativeness; with diffuse arrival of information, short horizons enhance it. In the process closed-form solution to the dynamic equilibrium with long-term investors is derived.]